2017
DOI: 10.19030/jabr.v33i4.10001
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Board Characteristics On Corporate Social Responsibility Disclosure

Abstract: The purpose of this study is to explore the link between corporate governance characteristics and corporate social responsibility disclosure of listed companies in the Pakistan stock Exchange (PSX), Pakistan. A sample of 179 companies from financial and non-financial sectors are studied from 2009 to 2015. The data is collected from their annual reports and websites. Binary logistic regression analysis is employed to test the models. The results reveal that board size, number of meetings and board independence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 34 publications
5
40
1
5
Order By: Relevance
“…Furthermore, a significant positive relationship exists between board size and the level of CSR activities, which confirms previous studies' findings (Ali & Atan, 2013;Arani, 2016;Beji et al, 2020;Dias et al, 2017;Esa & Zahari, 2016;Isa & Muhammed, 2015;Jizi et al, 2014;Lau et al, 2016;Mousa et al, 2018;Naseem et al, 2017;Said et al, 2009;Zhuang et al, 2018) that bigger boards lead to more CSR activities in Kuwait. Firms with big boards may have more diversity and different experiences among directors, leading to efficient monitoring and disclosure of more CSR activities in their annual reports.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, a significant positive relationship exists between board size and the level of CSR activities, which confirms previous studies' findings (Ali & Atan, 2013;Arani, 2016;Beji et al, 2020;Dias et al, 2017;Esa & Zahari, 2016;Isa & Muhammed, 2015;Jizi et al, 2014;Lau et al, 2016;Mousa et al, 2018;Naseem et al, 2017;Said et al, 2009;Zhuang et al, 2018) that bigger boards lead to more CSR activities in Kuwait. Firms with big boards may have more diversity and different experiences among directors, leading to efficient monitoring and disclosure of more CSR activities in their annual reports.…”
Section: Resultssupporting
confidence: 88%
“…H2: Ownership concentration by the government negatively impacts CSR activities. 2013 In term of board size, with the exception of one study (Abu-Sufian & Zahan, 2013), all previous studies discussed herein found a positive relationship between board size and CSR activities (Abu-Qa'dan & Swuaidan, 2019; Ali & Atan, 2013;Arani, 2016;Beji et al, 2020;Dias et al, 2017;Esa & Zahari, 2016;Isa & Muhammed, 2015;Jizi et al, 2014;Lau et al, 2016;Mousa et al, 2018;Naseem et al, 2017;Said et al, 2009;Zhuang et al, 2018), implying that big board size provides shareholders and stakeholders with high CSR activities. However, this study still supports the argument of agency theory that a small number of board directors has a positive impact on firms' controlling and monitoring (Jensen & Meckling, 1976;Yermack, 1996).…”
Section: Hypothesis Developmentmentioning
confidence: 62%
“…Nevertheless, despite the findings mentioned above, other studies did not find that CSR disclosure had any relationship with the presence of women on director boards [68,72,[136][137][138]. All in all, the literature review produced diverging findings regarding the influence of women's board presence on CSRD.…”
Section: The Relationship Between Women On Boards and Csrdmentioning
confidence: 83%
“…NPF becomes a crucial financial ratio in the banking sector and how to handle it will always be an intensive discussion. According to Naseem et al (2017), a large number of board meetings can handle the business operation of the organization. Furthermore, the more often the BOD organizes meetings, the risk of credit will be more intensively monitored and thus the NPF is expected to be controlled.…”
Section: Board Of Directors and Credit Risk: An Empirical Study Of Inmentioning
confidence: 99%